James Baldwin and Toni Morrison: Comparative Critical and Theoretical Essays - King, Lovalerie. author. aut Link
IX, 300 p.
Keywords: This collection of comparative critical and theoretical essays examines James Baldwin and Toni Morrison's reciprocal literary relationship. By reading these authors side-by-side, this collection forges new avenues of discovery and interpretation related to their representations of African American and American literature and cultural experience.